THE UTILIZATION OF INFORMATION TECHNOLOGY AS LEARNING MEDIA - Fitrani Dinda Fadhilah; Fitri Handayani Harahap; Nur Zarit Sofia; Suhendri Prayoga; Muhammad Taufik Ihsan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
The development of information and communication technology build it straightforward to speak in exchanging information in order that place, time and distance are not any longer obstacles. Moreover, through the internet data services are often accessed as learning resources within the world of education should be ready to follow the event of technological science. Therefore the use of technology within the style of learning media may be an alternate to beat the constraints of house and time of the prevailing learning method so lecturers don't got to make a case for thefabricto students in excess. In this article, the data were obtained from literature of study review and from other document analysis. Based on the study, The Utilization of information and communication technology in learning is carried out in order to increase effectiveness in the implementation of the learning process to improve student learning outcomes and the individual quality of students in terms of using technology more precisely and usefully.